Banking systems, capital markets, and financing the transformation of food systems: The role of macroeconomics, regulations, and incentives - Díaz-Bonilla, Eugenio; Zandstra, Tamsin (International Food Policy Research Institute, 2025)
Improving food systems requires significant expenditures and investments from both the public and private sector. In the case of public outlays, the decisions are taken by the government or by multilateral international organizations (with governments as their owners), while, obviously, private expenditures and investments depend on choices by the private sector. These private financial flows are guided by the decisions of consumers, producers, banking system institutions, and operators in capital markets. Public policy cannot dictate directly how those private actors act (for instance, governments cannot mandate that consumers must eat healthy diets), but it can influence those decisions through adequate macroeconomic, regulatory, and incentive frameworks. This discussion paper will focus briefly on some ideas about how those frameworks can reorient and expand current levels of funding towards food systems transformation, focusing particularly on banking systems and capital markets. First, it briefly analyzes the levels of financial flows in the banking system and capital markets. Then it looks at the role of macroeconomic policy in influencing the operations of food systems, followed by suggestions about other regulatory and incentive frameworks to create healthy, equitable, sustainable and climate-resilient food systems.